Theorizing effective (preventative) remedy: exploring the root cause dimensions of human rights abuse & remedy - Shivji, Alysha Kate (Journal of business ethics, 2025)
This paper puts forth a critical perspective on remedy for business-related human rights abuses. It reflects on the purpose of remedy in Business and Human Rights and argues that effective remedy should address the multiple root causes of abuses to prevent reoccurrences rather than focus on surface issues and isolated cases. To develop a theoretical framework to conceptualize preventative remedy that addresses multiple root causes, this research draws on Fraser’s radical democratic conception of justice and participatory parity. According to the principle, justice is achieved through social arrangements that enable all actors to engage with one another as peers. To conceptualize effective remedy as participatory parity, the paper examines three dimensions—cultural, economic, and political—where injustices or root causes of abuses must be addressed to realize participatory parity. The paper analyzes the illustrative case of the Fair Food Program through the lens of Fraser’s framework. Analysis reveals effective enforcement as necessary to realize participatory parity and address the three dimensions of justice in the context of severe power asymmetries. In the theorized framework, remedy aims to address the multiple root causes of business-related human rights abuses toward prevention and empower rightsholders to engage meaningfully in remedial processes.